Statelessness and citizenship : a comparative study on the benefits of nationality - Blitz, Brad K.; Lynch, Maureen (Maureen Jessica) (Cheltenham, UK ; Northampton, MA, USA : Edward Elgar, 2011)
The United Nations High Commissioner for Refugees estimates that there are more than 12 million stateless people in the world. The existence of stateless populations challenges some central tenets of international law and contemporary human rights discourses, yet only a very small number of states have made measurable progress in helping individuals acquire or regain citizenship. This fascinating study examines positive developments in eight countries and pinpoints the benefits of citizenship now enjoyed by formerly stateless persons. The expert contributors present an original comparative study that draws upon legal and political analysis as well as empirical research (incorporating over 120 interviews conducted in eight countries), and features the documentary photography of Greg Constantine. The benefits of citizenship over statelessness are identified at both community and individual level, and include the fundamental right to enjoy a nationality, to obtain identification documents, to be represented politically, to access the formal labor market and to move about freely. Gaining or reacquiring citizenship helps eliminate isolation and solicits the empowerment of individuals, collectively and personally. Such changes are of considerable importance to the advancement of a human rights regime based on dignity and respect.
Statelessness and the deprivation of nationality / Brad K. Blitz and Maureen Lynch -- Nationality and rights / Laura van Waas -- Citizenship in Kenya : the Nubian case / Abraham Korir Sing'Oei -- From erased and excluded to active participants in Slovenia / Jelka Zorn -- From statelessness to citizenship : up-country Tamils in Sri Lanka / P.P. Sivapragasam -- Citizenship reform and challenges for the Crimean Tatars in Ukraine / Rustem Ablyatifov -- The Urdu-speakers of Bangladesh : an unfinished story of enforcing citizenship rights / Katherine Southwick -- Mauritania : citizenship lost and found / Julia Harrington Reddy -- Statelessness, citizenship and belonging in Estonia / Raivo Vetik -- Arabia's Bidoon / Abbas Shiblak -- Summary and conclusions / Maureen Lynch and Brad K. Blitz -- Epilogue / James A. Goldston.
Includes bibliographical references (pages 216-244) and index.
Keywords: Statelessness; Citizenship; Politics and Government; Citizenship; Statelessness